Publications of Paul M. Lloyd. (Hispanic Review)
Lists the publications of hispanist Paul Max Lloyd. Book entitled "Verb-Complement Compounds in Spanish"; Book entitled "From Latin to Spanish"; Article entitled "What Language Should We Teach."